Estudo teórico da fotodissociação da molécula diclorodifluorometano (CFC 12) aplicando métodos multiconfiguracionais de estrutura eletrônica - Nascimento, Mayzza Márcia Araujo do (2021)
Chlorofluorocarbons (CFCs) are synthetic compounds that have been very used in refrigeration systems, due to their great chemical stability. Nowadays, these compounds are known because they have an important contribution to reducing the concentration of stratospheric ozone. Although the use of CFCs was limited by the Montreal Protocol, the presence of these molecules in the atmosphere is a secular concern, in other words, they will react for a long time in atmosphere. Based on these facts, the importance of this work relies on the need for a better understanding of the photodissociative processes involving these compounds in atmosphere. Dichlorodifluoromethane (CF2Cl2), also known as CFC-12, was chosen in this study because it is one of the most abundant CFCs and it has a long-term life around 112 years. In addition, it has a high ozone depletion potential. Although the electronic structure of the molecule has been previously investigated, some mechanisms are still not understood. Therefore, the objective of this research was to investigate how properties of 25 excited singles states of valence and Rydberg, through calculations of electronic structure, as well as a photodissociation of the molecule, from the characterization of the Potential Energy Curves (PEC). For this, computational tools were used, such as the highly correlated methods MCSCF (CASSCF) and MR-CISD/MR-CISD+Q, performed with the COLUMBUS 7.0 program. An experimental geometry was used as a starting point for the calculations. The CAS (12.8) and CAS (12.12) active spaces were used, and the aug-cc-pVDZ and d-aug-ccpVDZ base sets. The results showed the importance of Rydberg states for this system because the inclusion of these states provided a better characterization of electronic transitions. The MR-CISD method, with the MR-CISD+Q extensibility correction, provided better results for the investigated states. The theoretical results obtained for the values of the vertical energies of the valence states were in good agreement with that observed experimentally. PEC revealed the existence of a local dissociative minimum in the 31A' state curve that favors the formation of the CF2Cl+ (11A') + Cl- (1S) ion channel, based on non-adiabatic events. Optimization and frequency calculations confirmed the structure of the [CF2Cl]+ Cl- pair, with a stability of 3.64 eV. It was possible to conclude that the study achieved the objectives proposed in its initial planning. It is hoped that this research will enable a better understanding of the photochemistry of the CF2Cl2 molecule.